'Spatial anarchy' versus 'spatial apartheid': rural housing ironies in Ireland and England. Issue 1 (1st January 2015) - Gkartzios, Menelaos; Shucksmith, Mark
Abstract: Rural planning and housing have provoked challenging debates in Ireland and England through periods of economic growth and, more recently, crisis and austerity. In this paper, we comparatively review an extensive literature in both countries relating to the formation of their planning systems and cultural predispositions surrounding rural housing development. We highlight that in both cases selective constructions of rurality have shaped policy discourses surrounding rural housing provision that aimed to implement policies prioritising homeownership in Ireland, and environmental conservation in England. Both selective ruralities, however, have produced compromised outcomes, discussed here as 'spatial anarchy' and 'spatial apartheid' respectively.